R. H. Clark, The Code of the State of Georgia Page 817-818 (1873) § 4527 - (:unkn) unknown (General Publisher, 1870)
Prohibited the concealed carry of any pistol, dirk, sword in a cane, spear, Bowie knife, or any other kind of knives manufactured and sold for the purpose of offense or defense.
--
Keywords: CARRY - CONCEALED